Analysis of Factors Affecting Nurse Performance - Warizki, Nanda Putri; Farhan, Fazni; Eliza, Yulina (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2024)
The problem is the factors that affect performance, namely, workload, work stress, and work environment with a sample of 60 respondents. The method used is Multiple Linear Regression. The results show that work stress and work environment have a significant effect on performance, conversely workload does not have a significant effect on performance. This means that the higher the level of workload, the lower the performance produced by employees. The implication is that work stress and work environment must provide employee comfort in doing their work so that they do not have high work stress in working due to busy working hours, noise, non-conducive room temperature and conflicts and pressures in this Hospital. The work environment provides safe comfort so that employees are not disturbed in doing their work